2016
DOI: 10.1371/journal.pone.0155447
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake among Adolescents in a Middle-Income Country: An Outcome from the Malaysian Health and Adolescents Longitudinal Research Team Study (the MyHeARTs Study)

Abstract: Optimal nutrition is essential for healthy growth during adolescence. This study aims to investigate the baseline nutritional intake of Malaysian adolescents by gender, body mass index, and places of residence, both urban and rural. A cohort study was conducted consisting of 794 adolescents (aged 13-years) attending 15 public secondary schools from the Central (Kuala Lumpur and Selangor) and Northern (Perak) Regions of Peninsular Malaysia. Qualified dietitians conducted a 7-day historical assessment of habitua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 29 publications
2
43
0
Order By: Relevance
“…This may because more female students (84.8%) were involved. A previous study showed that male students had significantly higher energy intake than females (Abdull Hakim et al, 2012;Abdul Majid et al, 2016). As compared to the previous study by Zainuddin (2015), the present study shows a lower median energy and carbohydrate intake but higher fat intake among undergraduate respondents.…”
Section: Discussionsupporting
confidence: 50%
“…This may because more female students (84.8%) were involved. A previous study showed that male students had significantly higher energy intake than females (Abdull Hakim et al, 2012;Abdul Majid et al, 2016). As compared to the previous study by Zainuddin (2015), the present study shows a lower median energy and carbohydrate intake but higher fat intake among undergraduate respondents.…”
Section: Discussionsupporting
confidence: 50%
“…In general, adolescent diet has been reported to be high in fat and sugar and low in vitamins and minerals (23,46). Large quantities of fast food consumption and energy dense food is a reason for high-calorie diet in most adolescents (47). A systematic review on Malaysian adolescents revealed that high consumption of energy, macronutrients and skipping meals have an effect on cardio-metabolic health (48).…”
Section: Discussionmentioning
confidence: 99%
“…However, the seven-day diet history was chosen for this study, as this method has produced more valid estimates of energy intake in children and adolescents compared to other methods [24,32]. The tool was pretested on 40 participants from two different schools (one school each from an urban and rural area, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Most of the bone studies among adolescents did not assess the dietary intake, thereby limiting further analyses on the correlation between dietary intake and serum micronutrient status [22,23]. However, in this study, a validated seven-day diet history tool was used to estimate the actual habitual dietary intake among adolescents [24,25,26,27]. …”
Section: Introductionmentioning
confidence: 99%